Pengaruh Orientasi Pasar, Konsumen, Merek, dan Inovasi Layanan terhadap Kinerja UMKM di Yogyakarta - Hasan, Ali (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2019)
This study seeks to assess the relationship between Micro, Small and Medium Enterprises (MSME) firm performance and market orientation, customer orientation, brand orientation and service innovation in develop for all business. In past, very few studies have focused on the effect of marketing related variables on MSMEs. This study aspires to put some insight on this. Data were collected from creative industry MSME business firm entrepreneurs located in Yogyakarta, A total of 91 MSME entrepreneurs were surveyed in the study through adopting tested survey questionnaires from the past literature. Correlation and regression analysis were used to test the hypotheses. Result indicates that market orientation, customer orientation, brand orientation and service innovation have a positive direct influence on MSME performance.